Relevansi Putusan Uji Materi oleh Mahkamah Konstitusi terhadap Sistem Checks and Balances dalam Pembentukan Undang-Undang - Despan Heryansyah; Harry Setya Nugraha (Fakultas Hukum Universitas Jambi, 2019)
This article discusses the relevance of the judicial review decision by the Constitutional Court to the checks and balances system in law legislation in Indonesia. In the framework of checks and balances between state institutions, the existence of the authority of the Constitutional Court to examine laws against the Constitution can be seen as a limitation for the legislators. This is because the discretion of legislators, namely the President and the House of Representatives, in carrying out the legislation function can be limited by the interpretation of the Constitution carried out by the Constitutional Court. This article concludes, the checks and balances mechanism regulated in the 1945 Constitution of the Republic of Indonesia is realized with the principle of power limited by power. Therefore, the authority and decision of the judicial review by the Constitutional Court is not an intervention on the authority of lawmakers so that it isi assumed to pass the checks and belances principle. The authority and decision of the judicial review by the Constitutional Court actually confirms the manifestation of the principle of power limited by power and affirming the supremacy of the Constitution. Thus, the principle of supremacy of the Constitution in the context of the rule of law places the Constitution as the highest law. Abstrak Artikel ini membahas relevansi putusan uji materi oleh Mahkamah Konstitusi terhadap sistem checks and balances dalam pembentukan hukum berupa undang-undang di Indonesia. Dalam kerangka checks and balances antar lembaga negara, adanya kewenangan Mahkamah Konstitusi menguji undang-undang terhadap Konstitusi dapat dipandang sebagai suatu pembatasan bagi pembentuk undang-undang. Sebab, keleluasaan pembentuk undang-undang, yaitu Presiden dan Dewan Perwakilan Rakyat, dalam menjalankan fungsi legislasi bisa dibatasi oleh adanya tafsir Konstitusi yang dilakukan oleh Mahkamah Konstitusi. Artikel ini menyimpulkan, mekanisme checks and balances yang diatur dalam Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 diwujudkan dengan prinsip kekuasaan dibatasi oleh kekuasaan. Karena itu, kewenangan dan putusan uji materi oleh Mahkamah Konstitusi bukanlah wujud intervensi terhadap kewenangan pembentuk undang-undang dan melampaui prinsip checks and balances. Kewenangan dan putusan uji materi oleh Mahkamah Konstitusi justru menegaskan wujud dari prinsip kekuasaan dibatasi kekuasaan dan meneguhkan supremasi Konstitusi. Demikianlah, prinsip supremasi Konstitusi dalam konteks negara hukum yang menempatkan Konstitusi sebagai hukum tertinggi.